2023
DOI: 10.3390/ijms24087270
|View full text |Cite
|
Sign up to set email alerts
|

Mild Chronic Kidney Disease Associated with Low Bone Formation and Decrease in Phosphate Transporters and Signaling Pathways Gene Expression

Abstract: The initial phases of molecular and cellular maladaptive bone responses in early chronic kidney disease (CKD) remain mostly unknown. We induced mild CKD in spontaneously hypertensive rats (SHR) by either causing arterial hypertension lasting six months (sham-operated rats, SO6) or in its’ combination with 3/4 nephrectomy lasting two and six months (Nx2 and Nx6, respectively). Sham-operated SHRs (SO2) and Wistar Kyoto rats (WKY2) with a two-month follow-up served as controls. Animals were fed standard chow cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(172 reference statements)
0
1
0
Order By: Relevance
“…The importance of their biological role is undoubted. The FGF23 gene is a member of a large family of fibroblast growth factors [94], which is most associated with the KLOTHO gene in anti-aging processes [95]. A number of publications have examined the relationship of FGF23 and KLOTHO genes in physiological processes and in various diseases [96][97][98][99][100][101][102][103][104].…”
Section: Resultsmentioning
confidence: 99%
“…The importance of their biological role is undoubted. The FGF23 gene is a member of a large family of fibroblast growth factors [94], which is most associated with the KLOTHO gene in anti-aging processes [95]. A number of publications have examined the relationship of FGF23 and KLOTHO genes in physiological processes and in various diseases [96][97][98][99][100][101][102][103][104].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been found that MAPK signaling activation can inhibit Wnt signaling by up-regulating DKK1 protein. Consequently, Klotho, an upstream protein, acts as a co-receptor protein for FGF23, forming the FGF23-klotho complex, which can serve to activate the MAPK signaling pathway and exert biological effects [18][19] [20].…”
Section: Introductionmentioning
confidence: 99%